Orally administered β-glucan improves the hemolytic activity of the complement system in horses - Taline Scalco Picetti; Lucas de Figueiredo Soveral; Rovian Miotto; Luana Marina Scheer Erpen; Yasmin Kreutz; João Antônio Guizzo; Rafael Frandoloso; Luiz Carlos Kreutz (Veterinary World, 2021)
Background and Aim: Immune-modulating molecules mainly act on innate immune cells, which are central to early defense against invading pathogens and contribute to developing adaptive immunity. Yeast-extracted β-glucan, a model immune-modulating molecule, is widely used in several animal species; however, its effect on horse immune parameters has not been thoroughly investigated yet. This study aimed to evaluate the effects of orally administered β-glucan on selected innate immune parameters in horses.